Adaptive divergence in a scleractinian coral: physiological adaptation of Seriatopora hystrix to shallow and deep reef habitats - Bongaerts, Pim (BioMed Central, 2011)
BACKGROUND: Divergent natural selection across environmental gradients has been acknowledged as a major driver of population and species divergence, however its role in the diversification of scleractinian corals remains poorly understood. Recently, it was demonstrated that the brooding coral Seriatopora hystrix and its algal endosymbionts (Symbiodinium) are genetically partitioned across reef environments (0-30 m) on the far northern Great Barrier Reef. Here, we explore the potential mechanisms underlying this differentiation and assess the stability of host-symbiont associations through a reciprocal transplantation experiment across habitats ('Back Reef', 'Upper Slope' and 'Deep Slope'), in combination with molecular (mtDNA and ITS2-DGGE) and photo-physiological analyses (respirometry and HPLC). RESULTS: The highest survival rates were observed for native transplants (measured 14 months after transplantation), indicating differential selective pressures between habitats. Host-symbiont assemblages remained stable during the experimental duration, demonstrating that the ability to "shuffle" or "switch" symbionts is restricted in S. hystrix. Photo-physiological differences were observed between transplants originating from the shallow and deep habitats, with indirect evidence of an increased heterotrophic capacity in native deep-water transplants (from the 'Deep Slope' habitat). Similar photo-acclimatisation potential was observed between transplants originating from the two shallow habitats ('Back Reef' and 'Upper Slope'), highlighting that their genetic segregation over depth may be due to other, non-photo-physiological traits under selection. CONCLUSIONS: This study confirms that the observed habitat partitioning of S. hystrix (and associated Symbiodinium) is reflective of adaptive divergence along a depth gradient. Gene flow appears to be reduced due to divergent selection, highlighting the potential role of ecological mechanisms, in addition to physical dispersal barriers, in the diversification of scleractinian corals and their associated Symbiodinium.